Enhancing Chinese preschoolers’ executive function via mindfulness training: An fNIRS study - Xie, Sha; Gong, Chaohui; Lu, Jiahao; Li, Hui; Wu, Dandan; Chi, Xinli; Chang, Chunqi (Frontiers in Behavioral Neuroscience, 2022)
Mindfulness training has been found to enable cognitive and emotional awareness and diminish emotional distraction and cognitive rigidity. However, the existing intervention studies have largely focused on school children, adolescents, and adults, leaving young children unexplored. This study examined the influence of mindfulness training on young children using the one-group pretest-posttest design. Altogether 31 Chinese preschoolers (Mage =67.03 months, SD = 4.25) enrolled in a 5-week, twice-per-week mindfulness training. Their cognitive shifting, inhibitory control, and working memory were examined using a battery of executive function tasks. And their brain activations in the region of interest during the tasks were measured using fNIRS before and after the intervention. Results showed that their cognitive shifting and working memory tasks performance significantly improved, and their activation in the DLPFC significantly changed. Implications for this study were also included.